DESAIN FONDASI MASJID DI MAGETAN JAWA TIMUR - Aniek Prihatiningsih; Gregorius Sandjaja Sentosa; Alfred Jonathan Susilo; Kefas Januar; Josia Mariano Nicky Abel (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Foundation is an important work in the construction of a structure, because the foundation will carry and withstand the load of the building on top. A rock-solid building must have a firm foundation, where the foundation is able to withstand the load and transfer into the ground. Foundation of a structure must be able to minimize the potential of settlement or collapse. The purpose of this community service is to help fulfil the dream of the partner's extended family in building of a mosque. Recognizing the need for houses of worship in the Magetan area, partners are increasingly willing to donate their land and build a mosque as a house of worship for Muslims in Magetan. To realize these goals, partners are looking for experts in the field of Civil Engineering. Partners need civil engineering personnel to design the foundation of the mosque. The methodology for implementing community service activities is to prepare the necessary data such as location, soil test, government regulations, and load from the upperstructure. Before providing solutions to partners, regarding the foundation design of the mosque, partners are asked to conduct soil test at the site where the building will be constructed. The soil test consisted of 3 Cone Penetration Test (CPT) and 1 Bore Hole as well as laboratory tests. The location of the test is determined based on the building plan drawings. The results of this soil test will be the basis for calculating the foundation design. Solutions to problems from partners will be given in the form of a plan drawing of the foundation of a mosque building in Magetan in the form of a floor plan drawing of the foundation plan and the type of pilecap to be used and its reinforcement. The result of the planned foundation design is a drilled pile foundation with a depth of 16 m and a diameter of 400mm.